Optimasi Pemupukan Nitrogen pada Tanaman Sedap Malam Varietas Roro Anteng - Apriyadi, Farhan; Markam, Krisantini; Endah Retno Palupi; Cheong Min Kyoung; Yulia Rahmah; Krisantini (Jurnal Hortikultura Indonesia, 2025)
Tuberose (Polianthes tuberosa L.) is a popular cut flower in Indonesia, with excellent potential for development as a raw material for essential oils. Fertilization optimization is one of the efforts to meet the production needs of tuberose. This study aims to enhance the growth of tuberose plants and the production of flowers and bulbs of the Roro Anteng variety through optimized nitrogen fertilization. The research was conducted at Green Smart Farm Cikabayan, IPB University, from June to December 2023. The study employed a randomized complete block design (RCBD) with two factors: fertilizer doses of 600 kg ha-1, 450 kg ha-1, and 300 kg ha-1, and fertilization frequencies of 2, 3, and 4 times. The results showed that the nitrogen dose of 600 kg ha-1, with two applications, produced tuberose with more leaves than the doses of 450 kg ha-1 and 300 kg ha-1, and fertilization frequencies of three and four times. Different nitrogen doses and frequencies did not affect the number and quality of tuberose flowers. The nitrogen dose of 600 kg ha-1 produced more bulbs with larger sizes compared to doses of 450 kg ha-1 and 300 kg ha-1. However, the flowers’ highest flavonoid and phenol content was achieved with fertilization with a dose of 450 kg ha-1 applied three times. Keywords: dose fertilizer, frequency fertilizer, flower production, tuber production